Constructing and Reconstructing the "Rural School Problem": A Century of Rural Education Research. (March 2016) - Biddle, Catharine; Azano, Amy Price
This chapter examines 100 years of rural education research in the context of the demographic, migratory, economic, and social changes that have affected rural America in the past century. The authors conducted a systematic review of the literature on rural teacher recruitment, retention, and training as a case study to examine the constancy and change in the construction of the "rural school problem, " a concept drawn from early work by urban education reformers. They found that attention to rurality as a factor affecting education boomed in the first half of the 20th century thanks to a commitment to achieving a kind of modernity, an emphasis that waned in the second half of that century when modernity was believed to have been more or less achieved. Neoliberal economic policies and the precariousness of rural economies revived interest in the resilience and adaptability of rural America in the late 20th and early 21st centuries, however, leading to a renaissance in rural education research but one largely restricted to a few subfield journals. The authors discuss the implications of these trends for the future of rural education research, including the use of place as a lens for considering education.